Public Management : Old and New - Laurence E. Lynn (Routledge, 2006)
Offering much more than a purely theoretical or retrospective view of public management, this exciting text is an invaluable new addition to the field of public management. Putting the American model in perspective, it establishes the historical, theoretical, analytical, practical and future foundations for the comparative study of public management.